MORALITY IN THE SHADOW OF POLITICS - Devji, F (2010)
Having put an end to his first great movement of non-cooperation following the First World War, Gandhi sat down to learn the lessons of this early experiment in mass politics. In 1926 he went on to impart these lessons to his fellow workers in the Sabarmati Ashram by way of a series of lectures on the Bhagavad Gita. Gandhi was interested in exploring the relations between violence and non-violence, which he thought were so intimate that one could very easily turn into the other. Seeking out the Archimedean point that made such a turning possible, the Mahatma had occasion to criticize any ethics that would divide good from evil on the basis of a moral calculus. How, he asked, was an ethics possible that recognized the intractability of ignorance and compulsion? Any ethical system that relied upon knowledge and choice, he thought, was either deluded or true only for a very small elite. A common ethics, then, had to be one which recognized ignorance and compulsion not negatively, as posing limits to moral life, but rather in the form of positive virtues like duty and obedience. Gandhi's commentary on the Gita was therefore an attempt to think about moral action in the context of ignorance and compulsion, which he did by focusing on the integrity of the act itself divested of the idealism lent it by any moral calculus. Copyright © Cambridge University Press 2010.